Islamic Banking in Bangladesh: Challenges and Prospects - Shaown, Jubairul Islam; Sultana, Yesmin (AIUB Journal of Business and Economics, 2017)
Starting its journey in 1983, Islamic banking has been gaining increasing market share of the total banking industry; 8 full-fledged Islamic banks, along with 19 Islamic banking branches and 25 Islamic banking windows, hold more than 20% market share in total banking deposits and 23% in credit. This percentage of share has made Bangladesh one of the 12 systematically important jurisdictions in the world. This industry, compared to its conventional counterpart, is also performing well in many aspects such as ROI and NPL. The scenario changes when the banking scenario of other Muslim countries with similar demographics and economic status are compared with. The Islamic banking scenario in Bangladesh could be made more robust if the challenges in the way were properly addressed. The absence of a comprehensive Shariah based framework to bring all the related industry players under one umbrella is one of the most crucial factors hindering growth. Terrorist financing propaganda, lack of diversified service portfolio, insufficient product innovation and absence of skills and product knowledge training are few of the other challenges to be addressed. Even though, throughout the world, 60% of the Islamic banking customers are non-Muslims, in Bangladesh, this segment is not yet targeted as the Islamic products are, even now, offered to customers using religious appeal rather than pitching product qualities and professional benefit. If Bangladesh is to reach its fullest potential in this segment of banking, steps from multiple front need to be taken. The untapped non-Muslim customer segment penetration can be the first step. Partnering with NGOs and thus tapping further into micro-finance, public project financing through Shariah based syndication, creating a corporate governance culture by training Islamic finance analysts, and bringing in stress testing modules to check the resilience of Islamic banking in the country for different categories of financing are the few ways towards further growth in this industry. In order to bring out the potential growth, there has to be a strategic time bound roadmap setting out all the landmarks to be achieved.